Consequences of delaying non-urgent surgeries during COVID-19: a population-based retrospective cohort study in Alberta, Canada - Danielle A Southern; Khara Sauro; Mary Brindle; Shabnam Vatanpour; Cathy Eastwood; Adam G D'Souza; Ayoola Ademola; Abigail Thomas; Seremi Ibadin (BMJ Open)
Objectives To ensure sufficient resources to care for patients with COVID-19, healthcare systems delayed non-urgent surgeries to free capacity. This study explores the consequences of delaying non-urgent surgery on surgical care and healthcare resource use.Design This is a population-based retrospective cohort study.Setting This study took place in Alberta, Canada, from December 2018 to December 2021.Participants Adult patients scheduled for surgery in Alberta during the study period were included.Primary and secondary outcomes measures The proportion of surgeries completed and surgery wait time were the primary outcomes. The secondary outcomes were healthcare resource use (hospital length of stay, emergency room visits and physician visits). The association between the primary outcomes and patient and surgery-related variables was explored using regression.Results There were 202 470 unique patients with 259 677 scheduled surgeries included. Fewer surgeries were completed throughout the pandemic compared with before; in the fourth wave, there was a decrease from 79% pre-COVID-19 to 67%. There was a decrease in wait time for those who had surgery completed during COVID-19 (from 105 to 69 days). Having surgery completed and the wait for surgery were associated with the geographical zone, COVID-19 wave, and the surgery type and priority. There was a decrease in all measures of healthcare resource use and an increase in hospital and all-cause mortality during COVID-19 compared with before COVID-19.Conclusions The change in the proportion of scheduled surgeries completed and the wait time for completed surgery was modest and associated with COVID-19 wave and surgery-related variables, which was aligned with policies enacted during COVID-19 for surgery. The decrease in healthcare resource use suggests the effects of the COVID-19 pandemic may be delayed and may result in many patients presenting with advanced disease requiring surgical care.